Особливості технології безалкогольних напоїв з використанням дикорослої ягідної сировини - Романова, З. М.; Косоголова, Л. О.; Арутюнян, Тетяна Володимирівна (НТУ "ХПІ", 2015)
В работе рассмотрены направления повышения качества безалкогольных напитков, их конкурентоспособности на отечественном рынке путем оптимизации технологии с использованием полупродуктов на основе дикорастущего ягодного сырья.

The paper considers directions of increase the quality of soft drinks, their competitiveness in the domestic market by optimizing technology using intermediates based on wild berries.
Features of technology soft drinks with the use of wild berries
Keywords: водно-спиртові екстракти; хімічний склад; глюкозо-фруктозний сироп; ГФС; морс; купаж